The rise and fall of the right of silence - Quirk, Hannah (A GlassHouse book, 2017)
The right of silence : a benchmark of justice? -- The right of silence : a crime control target? -- Police custody, cop culture and the caution -- A "fundamental dilemma" : the undermining of legal representation at the police station -- Silence in court conclusion : the transformed landscape of the criminal trial